Many Balls in the Air Make Time Fly: The Effect of Multitasking on Time Perception and Time Preferences - Hjördis Hardardottir (Lund University, School of Economics and Management, Department of Economics, 2019)
In this paper, we study how increasing the cognitive demands of multitasking affects time preferences. The novelty of this paper is that it studies how time perception mediates the effect of multitasking on time preferences. Results from experimental psychology have demonstrated that people tend to experience the passage of time as quicker when they are busy with cognitively-demanding tasks. If time is experienced as passing faster, the future should be experienced as being closer, and patience should increase. However, a standard prediction from behavioral economics is that being cognitively loaded leads to less patient decisions. Our hypothesis is that increases in patience, driven by the speeding up of time, and decreases in patience, driven by decreased cognitive capacity, added together explain the total effect of increasing the cognitive demands of multitasking on time preferences. We also shed light on whether the observed relationship between time preferences and time perception within subjects is mirrored when comparing between subjects.
Keywords: C91; D91; 330; Time preferences; Multitasking; Cognitive load; Time perception; Foundations of preferences